The Catholic Church and Anti-Fascist Resistance in Istria and the Kvarner Littoral During the Second World War - Andrea Roknić Bežanić (Токови историје)
The paper presents the role of local Catholic priests from Istria and the Kvarner Littoral in the fight against fascism and Nazism. The research is based on pertinent literature, archival sources and periodicals, offering a novel perspective on the origins of the anti-fascist spirit in the mentioned regions.